Integration or Immersion? A Comparative Study at the Tertiary Level - Miriam Fernández-Santiago (Universidad de La Sabana, 2011)
The implementation of new degrees in the Spanish university system as a result of the process of adaptation to the European Space of Higher Education (ESHE) will bring significant changes in the learning of foreign languages at this level. Different methodological approaches such as foreign linguistic immersion in the content classroom or Content and Language Integrated Learning (CLIL) might be used as a compensatory curricular strategy for the learning of foreign languages in the implementation of the new university degrees. The present article reports on research conducted at the School of Psychology of the University of Granada (Spain) where these two methodological approaches were contrasted for an assessment of their efficiency with regards to the specific learning purposes indicated above. The results obtained show the academic convenience of the implementation of CLIL methodology as a compensation strategy for the loss of courses on English for Specific Purposes at the tertiary level.